Economic development of Nigeria : the socialist alternative - Oni, Ola.; Onimode, Bade; Nigerian Academy of Arts, Sciences, and Technology ([Ibadan] : Nigerian Academy of Arts, Sciences, and Technology, 1975)
This book is a sequel to the political programme, The Nigerian people's manifesto, published by the Nigerian Academy of Arts, Sciences and Technology in January 1974. They provide political and economic alternatives to the programmes of neocolonial forces in Nigeria in the early and mid-1970's. Some topics covered in the book include: economic programme and class struggle; critique of the present socioeconomic system (foreign domination, waste, corruption and inequality); neocolonial capitalism vs social planning; development of natural resources; industrial revolution; agrarian revolution, commercial revolution and others.
Includes bibliographical references: p. 260-262.
lje 03/09/2018
Loans
Keywords: Socialism; Economic development; Nigeria